ANALISIS FINANSIAL USAHA SAPI PERAH DENGAN CARA BAGI HASIL (Paro) DI PETERNAK - Supardi Rusdiana (Universitas Sulawesi Barat, 2019)
The study was conducted in Cikoneng Village, Pasirjambu Subdistrict, West Bandung Regency, Bandung West Java Province in 2018. The study used a survey of 27 dairy farmers in a way to share the results (Paro). Primary data and secondary data were analyzed descriptively, quantitatively and economic analysis. The purpose of this study is to analyze the financial economy of dairy cattle business by means of profit sharing (Paro) in farmers. The results of the study show that milk production of dairy cows produced by farmers every day is an average of 14.12 liters/day. Production costs for dairy cattle business are IDR.300.317.000 /year. The results of the calculation of breeder labor with the amount of labor costs amounting to IDR.5.635.000/year or 276.75/Hok/year.The advantages of farmer IDR 2.187.808/month with B/C of 2.3. Dairy cows belonging to farmers and property owned by investors are still maintained by the dignitaries, as investments, to produce calves and milk production. Economically, the financial value of B/C >1, or the business of dairy cows for profit sharing (Paro), can continue the business.